A numerical analysis on the performance of DHW storage tanks with immersed PCM cylinders. (October 2021) - Pop, Octavian G.; Balan, Mugur C.
Highlights: Original model to investigate the performance of storage tanks with solar coil and PCM. Simulation of storage tanks that serve a public swimming pool. Simulation of storage tanks' operation in different working conditions. Abstract: Thermal energy storage tanks have a fundamental role in the preparation and simultaneous distribution of domestic hot water. These tanks are supplied with thermal energy via classical means, based on electrical energy and fuel combustion, and via renewable energy sources. This study investigates the possibility of reducing the storage tank's accumulation volume by employing phase change materials to store high densities of thermal energy at constant temperatures. A mathematical model was developed to simulate the operation of storage tanks equipped with immersed solar coil, also taking into account the addition of phase change materials encapsulated in cylindrical containers. The mathematical model was validated based on literature data. The simulation program also determines the temperature of the primary heat transfer fluids, prepared by a solar collector system and a flat plate heat exchanger coupled with a gaseous fuel boiler. The program was used to study the performance of storage tanks that serve a public swimming pool, a type of building that is characterized by a high demand of domestic hot water. To the best knowledge of the authors, this scenario was not reported in the literature. The study revealed that the nominal volume of the storage tanks can be reduced by 25% in comparison to the classic alternative, by using phase change materials as thermal storage. Also, the tanks equipped with phase change material achieved a reduction of fuel consumption and CO2 emissions by (5.00-11.97) % in comparison to the classic solution.